Extensive Nonsegmental Pulmonary Perfusion Defects on SPECT/CT as an Early Sign of COVID-19 Infection - Franceschi, Ana M.; Matthews, Robert; Ahmed, Osama; Mourtzikos, Karen; Bajc, Marika; Franceschi, Dinko (World Journal of Nuclear Medicine, 2022)
We describe a hospitalized patient with confirmed coronavirus disease 2019 in whom the initial chest computed tomography (CT) was negative, while subsequent perfusion single-photon emission computed tomography/computed tomography imaging revealed extensive nonsegmental perfusion defects in addition to newly developing parenchymal densities. Possible reasons for these findings and their relationship to the multisystem severe acute respiratory syndrome coronavirus 2 infection are discussed in this article.
Keywords: pulmonary embolism; perfusion imaging; SPECT/CT; COVID-19; inflammation; pneumonia